Flexible structured illumination microscope with a programmable illumination array - Křížek, Pavel; Raška, Ivan; Hagen, Guy M (Optics express, 2012)
Structured illumination microscopy (SIM) has grown into a family of methods which achieve optical sectioning, resolution beyond the Abbe limit, or a combination of both effects in optical microscopy. SIM techniques rely on illumination of a sample with patterns of light which must be shifted between each acquired image. The patterns are typically created with physical gratings or masks, and the final optically sectioned or high resolution image is obtained computationally after data acquisition. We used a flexible, high speed ferroelectric liquid crystal microdisplay for definition of the illumination pattern coupled with widefield detection. Focusing on optical sectioning, we developed a unique and highly accurate calibration approach which allowed us to determine a mathematical model describing the mapping of the illumination pattern from the microdisplay to the camera sensor. This is important for higher performance image processing methods such as scaled subtraction of the out of focus light, which require knowledge of the illumination pattern position in the acquired data. We evaluated the signal to noise ratio and the sectioning ability of the reconstructed images for several data processing methods and illumination patterns with a wide range of spatial frequencies. We present our results on a thin fluorescent layer sample and also on biological samples, where we achieved thinner optical sections than either confocal laser scanning or spinning disk microscopes.
Keywords: Lighting; Pliability; Silicon; Microscopy; Liquid Crystals; ohebnost (fyzika); kalibrace; mikroskopie; osvětlení; Calibration; křemík; kapalné krystaly